Enhanced Properties of Palm Oil Boiler Clinker Concrete with Sang Yod Rice Husk Ash - Tonnayopas, Danupon; Kueaket, Kamolchanok (Journal of Advanced Research in Applied Mechanics, 2020)
Laboratory experiments of this investigation are to reclaim palm oil boiler clinker (POBC) as coarse aggregate for concrete and partially replaced Portland cement type 1 with Sang Yod rice husk ash (SYRHA) in proportion of 10%, 20% and 30wt.%. Characterization of POBC aggregate was carried out on grain size distribution and shape analysis, specific gravity, loose and compacted bulk density, water absorption, organic impurity, aggregate impact value and Los Angeles abrasion. Each mixing specimen was kept water to binder ratio at 0.42 throughout this study and varied duration of curing in water for 7, 28 and 56 days. The properties of paste and harden cube concrete in size 10×10×10 cm including setting time, bulk density, water absorption and compressive strength and were determined. According to aggregate testing results indicated that POBC was met the specification of normal-weight aggregate. Addition of SYRHA decreased both setting time and hydration temperature of paste. Furthermore, concrete contained 20% SYRHA provided highest 56-day compressive strength of 53.12 MPa and increased water absorption of 5.27%.